Properties and structure of tungstencarbide – cobalt coatings deposited by the APS - plasma spray process - Mrdak, Mihailo Rade (Vojnotehnički glasnik / Military Technical Courier, 2013)
The aim of this study was to optimize the parameters of the plasma spray and to deposit WC17Co layers with optimal structural - mechanical characteristics. The powder was deposited by the plasma spraying process at the atmospheric pressure (APS). When choosing the parameters, the flow of the He plasma gas was taken as the basic parameter. In relation to other gases, helium does not react with the powder,it produces a denser plasma with a lower heat content and it incorporates less ambient air into the plasma jet which reduces decarburization of the powder. The study shows three groups of samples obtained with three plasma gas flows of 12, 22 and 32 l/min He. The coating with the best properties was deposited on the shaft sleeve of the main rotor of the Gazelle H42 helicopter, in order to reduce the influence of vibrations and bearings on sleeve wear up to 500°C. The estimates of the WC17Co layers of the coating were made on the basis of their structural - mechanical properties. The surface morphology of the WC17Co powder particles was examined on the SEM. The mechanical properties of the deposited coatings were tested in accordance with the ‘TURBOMECA’standard. The estimate of the mechanical properties of layers was done by examining microhardness with the method HV0.3 and bond strength with tensile testing. Metallographic assessment of the pore proportion in the layers of the WC17Co coating (image analysis) was performed with the technique of light microscopy in accordance with the ‘Pratt & Whitney’ standard. Studies have shown that the rate of the plasma gas flow significantly affects the mechanical properties and the structure of coatings.